Binocular luster – A review. (May 2022) - Wendt, Gunnar; Faul, Franz
Abstract: Binocular luster is a visual phenomenon that can be elicited by dichoptic stimuli showing an interocular difference in color or luminance contrast. For instance, when the two eyes are presented with simple center-surround stimuli in which the center patch in one eye is brighter and in the other eye darker than the common surround, the center patch in the fused percept assumes a lustrous appearance reminiscent of metal or graphite. Soon after the discovery of this phenomenon in the mid-19th century, it was intensively studied and several explanations were proposed. After this initial phase, however, research interest waned significantly. Stimulated by new insights into related phenomena and the underlying physiological mechanisms, the last 20 years have seen an increase in research activity in this field, which has considerably expanded our understanding of binocular luster. In this paper, we provide a detailed review of research on binocular luster over the past 170 years. We present and discuss the existing findings in a number of separate sections, dealing with 1) the phenomenology of binocular luster, 2) different theories that have been proposed, 3) several factors influencing the lustrous impression, 4) the relationship between binocular luster and binocular rivalry, 5) the current understanding of its neural basis, and 6) potential applications based on binocular luster.